2016
DOI: 10.1007/s11295-016-1000-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation for needle traits in Scots pine (Pinus sylvestris L.)

Abstract: 10The remnants of the Caledonian Native Pinewood are distributed across a relatively narrow

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…As phenological marks, needles are directly exposed to the environment's physical factors, such as altitude, air temperature, atmospheric pressure, precipitation, and wind velocity (Friend & Woodward, 1990;Körner, 2007;Tiwari et al, 2013). They are also responsible for photosynthesis, carbon assimilation, and exchange of gas and water, and they may vary in overall dimensions, as well as in details of key anatomical characteristics important in processes of adaptation (Donnelly et al, 2016). Cone formation is also known to be variable, depending greatly upon climatic factors (Ovington, 1957).…”
Section: Introductionmentioning
confidence: 99%
“…As phenological marks, needles are directly exposed to the environment's physical factors, such as altitude, air temperature, atmospheric pressure, precipitation, and wind velocity (Friend & Woodward, 1990;Körner, 2007;Tiwari et al, 2013). They are also responsible for photosynthesis, carbon assimilation, and exchange of gas and water, and they may vary in overall dimensions, as well as in details of key anatomical characteristics important in processes of adaptation (Donnelly et al, 2016). Cone formation is also known to be variable, depending greatly upon climatic factors (Ovington, 1957).…”
Section: Introductionmentioning
confidence: 99%
“…Scots pine is wind‐pollinated, enabling reproduction across large distances; however, in Scotland, it has been shown that asynchrony in flowering phenology may serve to inhibit gene flow among populations (Whittet, Cavers, Cottrell, Rosique‐Esplugas, & Ennos, ). Related work on needle anatomical traits has shown differentiation for stomatal band and resin canal densities, consistent with adaptation to the same longitudinal rainfall gradient that generates adaptive differences in flood tolerance in P. sylvestris in Scotland, is also modest (Donnelly et al., ).…”
Section: Discussionmentioning
confidence: 80%
“…This systematic evaluation of fixed‐effects combinations is similar to that described by Burnham and Anderson () and Grueber, Nakagawa, Laws, and Jamieson (). Rainfall and longitude at site of origin were included as covariates, the latter having previously shown potential to be a more effective predictor of trait variation in Scotland than raw meteorological data (Donnelly et al., ). The best models were then refitted using restricted maximum likelihood.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in needle characteristics is also in congruence with Fowler and Morris (1977) in Pinus resinosa, Sagwal (1978) in P. roxburghii, Rajendra (2009) in P. merkusii, Nikolic et al (2013) in Picea omorika, Nikolic et al (2014) in Pinus heldreichii, Boratynska et al (2014) in P. mugo, Nikolic et al (2015) in P. peuce and Donnelly et al (2016) in P. sylvestris and Huang et al (2016) in Pinus yunnanensi.…”
Section: Variability Estimatesmentioning
confidence: 71%